Hubungan Kualitas Pelayanan Keperawatan dengan Tingkat Kepuasan Pasien di Rumah Sakit Pertamina Bintang Amin Husada Kota Bandar Lampung - Nur Hidaya Tulaisyah; Usastiawaty Cik Ayu Saadiah Isnainy; Aryanti Wardiyah (Universitas Malahayati Lampung, 2022)
ABSTRACT The quality of hospital health services in Indonesia has been recognized internationally. This has been proven by the issuance of an accreditation certificate from The International Society for Quality in Health Care (ISQua) for the National Hospital Accreditation Standard. The National Hospital Accreditation Standard latest accreditation standard made by the Hospital Accreditation Commission independently. Pertamina Bintang Amin Hospital by taking a letter from the recapitulation of client satisfaction on the quality of nursing care for nurses, the results of patient and family perceptions are obtained with the criteria of nurses in the category of satisfied 86% and dissatisfied 14%. Meanwhile, for patient satisfaction with services at the hospital, 92% said they were satisfied, and 8% said they were not satisfied. This study aims to determine the relationship between the quality of nursing services and the level of patient satisfaction at Pertamina Bintang Amin Husada Hospital, Bandar Lampung City in 2022. The type of research used was quantitative, the research design used an analytical survey, with a cross-sectional approach. The population in this study were 783 patients who were hospitalized at Bintang Amin Hospital, while the sample was taken with the slovin formula so that the total number of respondents was 178 respondents. The sampling technique used purposive sampling. Analysis of univariate and bivariate data using chi-square test. This research was conducted from May to June 2022. Most of the quality of nursing services in the poor category with a percentage of 58.4%. Most of the patient satisfaction in the bad category as much as 57.3%. There is a relationship between the quality of nursing services and the level of patient satisfaction at Pertamina Bintang Amin Husada Hospital Bandar Lampung City in 2022 with a p-value of 0.000. This research can be used as input to improve the quality of nursing services in providing more services for patients, by means of nurses showing readiness when performing nursing services. Keywords: Quality of Nursing Services, Level of Satisfaction, Patients ABSTRAK Mutu pelayanan kesehatan rumah sakit di Indonesia telah diakui secara internasional. Hal tersebut telah dibuktikan dengan diberikannya sertifikat akreditasi The International Society for Quality in Health Care (ISQua) untuk Standar Nasional Akreditasi RS (SNARS). SNARS merupakan standar akreditasi terbaru yang dibuat oleh Komisi Akreditasi Rumah Sakit (KARS) secara mandiri. Rumah Sakit Pertamina Bintang Amin dengan melakukan pengambilan surat hasil rekapitulasi kepuasan klien terhadap kualitas asuhan keperawatan perawat didapat hasil persepsi pasien dan keluarga dengan kriteria perawat dengan kategori puas 86% dan tidak puas 14%. Sedangkan untuk kepuasan pasien terhadap layanan di RS 92% menyatakan puas, dan 8% menyatakan tidak puas. Penelitian ini bertujuan untuk mengetahui hubungan kualitas pelayanan keperawatan dengan tingkat kepuasan pasien di Rumah Sakit Pertamina Bintang Amin Husada Kota Bandar Lampung Tahun 2022. Jenis penelitian menggunakan kuantitatif, rancangan penelitian menggunakan survey analitik, dengan pendekatan crosssectional. Populasi dalam penelitian ini sebanyak 783 pasien yang melakukan rawat inap di Rumah Sakit Bintang Amin, sedangkan sampel diambil dengan rumus slovin sehingga didapat jumlah sebanyak 178 responden. Teknik sampling menggunakan purposive sampling. Analisa data univariat dan bivariat menggunakan uji chisquare. Penelitian ini dilakukan pada bulan Mei s/d Juni tahun 2022. Sebagian besar kualitas pelayanan keperawatan dengan kategori buruk dengan persentase 58.4 %. Sebagian besar kepuasan pasien dengan kategori buruk sebanyak 57.3 %. Ada Hubungan kualitas pelayanan keperawatan dengan tingkat kepuasan pasien di Rumah Sakit Pertamina Bintang Amin Husada Kota Bandar Lampung Tahun 2022 dengan hasil p-value 0.000. Penelitian ini dapat sebagai bahan masukan untuk meningkatkan kualitas pelayanan keperawatan dalam memberikan pelayanan yang lebih bagi bagi pasien, dengan cara perawat menunjukan kesiapan ketika melakukan pelayanan keperawatan. Kata Kunci: Kualitas Pelayanan Keperawatan, Tingkat Kepuasan, Pasien